THE USE OF INFORMATION GAP METHOD IN SPEAKING CLASS AT MTS RIYADLUL MUHTADIN PEGANTENAN PAMEKASAN IN THE ACADEMIC YEAR OF 2018/2019 - Syarif Hidayatullah; Tjitra Ramadhani (Universitas Madura, 2019)
This study is focus on the implementation of information gap method and the students` response to the implementation of information gap method in teaching speaking skill by one english teacher who taught twenty one students in IX IPS class at MTs Riyadlul Muhtadin Pegantenan Pamekasan. This study was aimed to describe the the use of Information Gap method in teaching speaking by considering the implementation of group work, choosing interesting material and applying some procedures, then they did the activities consisted of incomplete information in the form of text. Then each groups performed asking and question in front of the class to completing the task. This study also describe the students` response to Information gap method, there were 90.47 % of the students were attracted to learn by using Information Gap Method. Furthermore, the information-gap activities could grab the students’ attentions, make them enjoyed the material during the class, and enthusiastically joined the teaching and learning activities.